INHERITANCE OF FERTILITY RESTORATION OF FIVE SOURCES OF CYTOPLASMIC MALE STERILITY IN RICE (ORYZA SATIVA L.) - SAWANT, D.S.; KUNKERKAR, R.L; SHETYE, V.N.; SHIRDHANKAR, M.M. (Annals of Agricultural Research, 2014)
The cross combinations involving six male sterile lines of five different cytosterile sources viz., IR Â 58025 A and PMS 2 A (WA), IR 68885 A (Mutant-induced by gamma irradiation of IR 62829 B), IR 54755 A (ARC), G 46 A (Gambiaca) and D 297 A (Dissi), when crossed with five common restores viz., Ratnagiri 3, Swarna, IR 5, IR46 and IR 54, showed more than 80% spikelet fertility restoration in all the combinations except IR 54755 A x Swarna and IR 54755 A x IR 54. The F2 segregation classification based on pollen as well as spikelet fertility in the 28 cross combinations, indicated the presence of two independent dominant fertility-restoring genes. The mode of action of the two genes varied in different crosses revealing three types of interaction viz., epistasis with dominance, epistasis with incomplete dominance and epistasis with recessive. Change in fertility restoration by same restorer with CMS line of same source and different source could be due to the influence of female parent genotype or fertility restoring genes has different penetrance and is affected by modifier.